The Confidence Paradox: A Quantitative Study of Self-Confidence and Narcissistic Tendencies Among Junior High School Students on Social Media - Sri Rizqi Wahyuningrum; Amaliah Aryani (Universitas Islam Negeri Madura, 2026)
Self-confidence and narcissistic tendencies have a fairly complex relationship. Individuals with narcissistic traits often appear very confident, but in fact, they have a strong drive for admiration and social recognition. The phenomenon of increasing adolescent activity on social media, which often shows narcissistic behavior, such as showing off and seeking validation from others, is similar to what happened to students at SMPN 2 Pamekasan. This study used a comparative causal quantitative approach with simple linear regression. The instruments used were a questionnaire scale of self-confidence (X) and digital narcissistic tendencies (Y). The results showed a positive and significant influence of self-confidence on narcissistic tendencies on social media, with a significance value of 0,000 <0,05, and a magnitude of 20.%. This means that the higher a student's self-confidence, the higher the narcissistic tendencies shown on social media. This study concludes that self-confidence plays a role in shaping students' narcissistic tendencies in social media. Therefore, it is important for schools, guidance counselors, and parents to guide students to have healthy and moderate self-confidence without using it as a basis for seeking excessive validation in cyberspace.